Perekonomian di Masa Dinasti Umayyah: Sebuah Kajian Moneter dan Fiskal - Muhammad Dliyaul Muflihin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2020)
At the middle ages is a leadership period of Islamic Daula, it can be said that the Umayyad’s Dynasty was an aggressive dynasty in politics at that time. So many caliphs from the family of the Umayyad’s who led the country at that time. The reign is known as an aggressive era, as evidenced by efforts to expand the region, the expansion will certainly have an impact on fields, one of which is the economic field. This study aims to answer how economic policy patterns are seen from monetary and fiscal aspects at that time. This research uses a qualitative method with descriptive approach. The results of this study are that there are a number of policies carried out by the Umayyad Caliphs such as the Baitul Mal policy, the real sector policy and the regional autonomy policy that had an impact on the economy at that time, especially on monetary and fiscal matters, namely money arrangements and tax.